Treatment outcomes in VI nerve palsy corrected by Carlson & Jampolsky technique - Ejzenbaum, Fábio [UNIFESP] (2007)
PURPOSE: To study the results of Carlson & Jampolsky technique in 31 patients with VI nerve palsy. METHODS: We had 23 unilateral and 8 bilateral cases. The mean unilateral preoperative esotropia was 56.8 PD ± 24 PD (30 PD to 100 PD) and they had a mean postoperative follow-up of 14 ± 17.9 months (3 to 72). The mean bilateral preoperative esotropia deviation angle in primary position was 74.5 PD ± 20.7 PD (45 PD to 100 PD) and the mean postoperative follow-up was 14.7 ± 15.7 months (4 to 47). RESULTS: In the unilateral group, 18 patients had good results and reoperation was not necessary. Out of 5 patients who were reoperated (2 undercorrections and 3 overcorrections), 2 had to use prismatic glasses. Among the bilateral patients, 2 cases were reoperated (1 undercorrection and 1 overcorrection), and the undercorrected patient remained with esotropia (ET13 PD), and also had to use prismatic glasses. CONCLUSIONS: Carlson & Jampolsky technique was useful to treat patients with VI nerve palsy. We had low reoperation rates and, among the 7 patients who needed a second intervention, only 3 did not achieve good results.